Applying decomposed theory of planned behaviour (DTPB) in predicting individual's intention to purchase halal personal care products: The moderating role of spiritual intelligence / Sulaiman Nawawi - Nawawi, Sulaiman (Institute of Graduate Studies, UiTM, 2018)
A great deal of research has been conducted to predict the factors that may influence individual's intention to purchase halal personal care products. Numerous models such as theory of reasoned action (TRA) and theory of planned behaviour (TPB) have been applied and proposed to enhance the understanding of this issue. While the researcher may use any of these models, the decomposed theory of planned behaviour (DTPB) has, however, attracted the researcher's attention. Although DTPB was specifically tailored to understand the adoption of information technology (IT), antecedents such as interpersonal referents, self-efficacy, and resource-facilitating conditions can still be applied into research of other natures including that of halal personal care products. Therefore, this study will provide an interesting platform to explore the robustness of the theory in predicting one's behavioural intention within different research area, thus, contributing to our understanding of the factors that may influence individual's intention to purchase halal personal care products. By decomposing the attitudinal, normative, and perceived control beliefs into relevant multi-dimensional constructs, the researcher could expect to have a higher predictive power and a more precise understandings of the determinants of behaviour. Additionally, the understanding of this particular theory was further extended by integrating the moderating role of spiritual intelligence into the framework, thus, providing a significant contribution to the body of knowledge and literatures on halal personal care products…